Legal foundations for reforming public education in the Ukrainian SSR (1953–1960) - Omarova, Aisel (Український політико-правовий дискурс, 2025)
Following the significant political changes of 1953–1954, a gradual transformation of the education system throughout the Soviet Union began, but this was particularly pronounced in the Ukrainian SSR. After Stalin's death, the policy of de-Stalinisation initiated by Khrushchev laid the groundwork for large-scale reforms with one key reform area being education. In much of the social science scholarship, this reform has been examined primarily from pedagogical or socio-economic perspectives, whereas its political and legal dimensions have received comparatively little attention.This article analyses the legal, ideological and institutional foundations of public education system reform in the Ukrainian SSR during de-Stalinisation to ask these changes affected the structure, content and functions of schools. The methodological basis of the article consists of historical-legal, comparative-legal, and structural-functional methods, which made it possible to trace the relationship between political decisions, socio-economic needs, and changes in the educational policy of the Ukrainian SSR during the period of de-Stalinisation. Sources were selected based on the principles of representativeness and reliability, using regulatory and legal acts, party documents, and publications of official reports of the Ministry of Education of the Ukrainian SSR. Statistical data were analysed using a historical-dynamic method, which made it possible to identify trends in education coverage, student performance indicators, and the development of the network of educational institutions in the 1950s and early 1960s. The combination of quantitative analysis and qualitative interpretation of sources made it possible to reveal not only the formal indicators of the reforms, but also their real social impact. The results show that the 1958 reform, enshrined in the USSR Law and the Ukrainian SSR Law of the same name ‘On Strengthening the Connection Between School and Life and on the Further Development of the Public Education System,’ was twofold. The research concludes that the 1958 reform was a manifestation of Soviet modernisation policy aimed at forming a ‘new man’ — a disciplined worker loyal to the party and the state. Thus, the reform demonstrated the duality of the Soviet educational project, in which modernisation aspirations were combined with ideological control and the subordination of education to political goals. This work contributes to legal history by offering a comprehensive analysis of the 1958 reform as a legal instrument through which the Soviet state pursued its political and ideological objectives in the field of education.